The Golden Quadrilateral Highway Project and Urban/Rural Manufacturing in India - Ghani, Ejaz; Goswami, Arti Grover; Kerr, William R. (World Bank, Washington, D.C., 2013)
This study investigates the impact of the Golden Quadrilateral highway project on the urban and rural growth of Indian manufacturing. The Golden Quadrilateral project upgraded the quality and width of 5,846 km of roads in India. The study uses a difference-in-difference estimation strategy to compare non-nodal districts based on their distance from the highway system. For the organized portion of the manufacturing sector, the Golden Quadrilateral project led to improvements in both urban and rural areas of non-nodal districts located 0-10 km from the Golden Quadrilateral. These higher entry rates and increases in plant productivity are not present in districts 10-50 km away. The entry effects are stronger in rural areas of districts, but the differences between urban and rural areas are modest relative to the overall effect. The productivity consequences are similar in both locations. The most important difference appears to be the greater activation of urban areas near the nodal cities and rural areas in remote locations along the Golden Quadrilateral network. For the unorganized sector, no material effects are found from the Golden Quadrilateral upgrades in either setting. These findings suggest that in the time frames that we can consider -- the first five to seven years during and after upgrades -- the economic effects of major highway projects contribute modestly to the migration of the organized sector out of Indian cities, but are unrelated to the increased urbanization of the unorganized sector.